ANALISIS KRITIS TANTANGAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK SIKAP SOSIAL SISWA - Wulandari, Tri Retno; Kurniawati, Nur Indah; Muluk, M. Islah Azharul; Syafi'i, Imam (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
This research explores the challenges in Islamic Religious Education (PAI) in schools, especially those related to students' social attitudes. One of the main issues faced is segregation between religious knowledge and general knowledge, where religious education tends to focus on aspects of the afterlife, while general knowledge is considered only for worldly matters. In addition, ethical crises in diverse societies, such as radicalism and intolerance, are often triggered by a narrow approach to religious education that does not open up space for understanding differences. This research was conducted using a qualitative approach involving interviews  and literature studies to analyze the impact of these attitudes on students' social interactions and tolerance. Research findings reveal that it is very important to design a more inclusive and comprehensive approach to Islamic education, which combines religious knowledge with general knowledge, while instilling the values of tolerance, mutual respect and understanding of differences. Education based on moderation and inclusivity can be a solution to create a young generation who is more open, broad-minded, and able to live side by side in society.